Live fast, diversify non-adaptively: evolutionary diversification of exceptionally short-lived annual killifishes - Lambert, Joshua W. (BMC Evol Biol, 2019)
BACKGROUND: Adaptive radiations are triggered by ecological opportunity – the access to novel niche domains with abundant available resources that facilitate the formation of new ecologically divergent species. Therefore, as new species saturate niche space, clades experience a diversity-dependent slowdown of diversification over time. At the other extreme of the radiation continuum, non-adaptively radiating lineages undergo diversification with minimal niche differentiation when ‘spatial opportunity’ (i.e. areas with suitable ‘ancestral’ ecological conditions) is available. Traditionally, most research has focused on adaptive radiations, while empirical studies on non-adaptive radiations remain lagging behind. A prolific clade of African fish with extremely short lifespan (Nothobranchius killifish), show the key evolutionary features of a candidate non-adaptive radiation – primarily allopatric species with minimal niche and phenotypic divergence. Here, we test the hypothesis that Nothobranchius killifish have non-adaptively diversified. We employ phylogenetic modelling to investigate the tempo and mode of macroevolutionary diversification of these organisms. RESULTS: Nothobranchius diversification has proceeded with minor niche differentiation and minimal morphological disparity among allopatric species. Additionally, we failed to identify evidence for a role of body size or biogeography in influencing diversification rates. Diversification has been homogeneous within this genus, with the only hotspot of species-richness not resulting from rapid diversification. However, species in sympatry show higher disparity, which may have been caused by character displacement among coexisting species. CONCLUSIONS: Nothobranchius killifish have proliferated following the tempo and mode of a non-adaptive radiation. Our study confirms that this exceptionally short-lived group have diversified with minimal divergent niche adaptation, while one group of coexisting species seems to have facilitated spatial overlap among these taxa via the evolution of ecological character displacement. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12862-019-1344-0) contains supplementary material, which is available to authorized users.